Remodeling of the Basal Labyrinth of Retinal Pigment Epithelial Cells With Osmotic Challenge, Age, and Disease - Hayes, Matthew J. (2019)
Purpose: The basal surface of the retinal pigment epithelium (RPE) is folded into a complex basal labyrinth thought to facilitate solute and water transport. We aimed to analyze and define the structural organization of the basal labyrinth of the RPE to enable quantitative analysis of structural changes in age and disease and to better understand the relationship between basal labyrinth structure and efficiency of transepithelial transport. Methods: Conventional transmission and serial block-face scanning electron microscopy and electron tomography were used to examine the structure of the basal labyrinth in mouse eyes of different ages and genotypes and with and without osmotic shock before fixation. Results: We identified structurally distinct zones (stacked and ribbon-like) within the RPE basal labyrinth that are largely organelle free and cisternal elements that make contact with the endoplasmic reticulum (ER) and mitochondria. These zones are lost in a hierarchic fashion with age and prematurely in a model of the progressive retinal degenerative disease, choroideremia. Junctional complexes crosslink closely opposed infoldings. Spacing between the basal infoldings was affected by subtle osmotic changes while osmotic shock induced dramatic remodeling of the infoldings. Conclusions: The basal labyrinth has complex but ordered structural elements that break down with age and in choroideremia. The geometry of these elements and site of contact with ER and mitochondria likely facilitate the ion transport that drives water transport across the basal RPE surface. Changes in structure in response to local osmotic variation may allow transport to be modulated in order to maintain RPE volume.